ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN TURNOVER INTENTION PEGAWAI DI RSUD TUAN RONDAHAIM KABUPATEN SIMALUNGUN - Elli Rimarni Girsang (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2026)
Human resource management is necessary to support the achievement of the hospital's vision and mission. One of the problems in human resource management is that the desire to leave (intention to quit) can cause employees to decide to leave their jobs. The study was conducted among State Civil Service (ASN) employees at Tuan Rondahaim Regional Hospital. The number of planned staff turnover at Tuan Rondahaim Hospital in the 3 years from 2021 to 2023 all exceeds the standard (Leap in Lusiati 2013, 10-11%), the average is 12.23%. The research objective is to analyze factors related to employee turnover intention at Tuan Rondahaim Hospital. The study design used was cross-sectional. The study population was 52 people with a sample size of 52 people using the total sample. The results of bivariate analysis show that the variables related to intention to quit are reward factors (p=0.031), career development (p=0.031) and geographical factors (p=0.011), in Then the variables not associated with labor turnover intention are age (p=0.739), marital status (p=0.400) and workload (p=0.342). Multivariate analysis results show that the variable most related to intention to quit is the career development factor with Exp (B) of 10.752 (95% CI 2,000-57,794), meaning employees are not satisfied with the job. Current career development is a coefficient of 10.752 with intention to leave many times higher than employees who are satisfied with career development at Tuan Rondahaim Hospital. It is hoped that Tuan Rondahaim Hospital can provide employees with career development that is appropriate to their skills and sustainable.